Study of the Performance of Electrical and Mathematical Models of Electrostatic Precipitators in the Physical Cleaning of Air Pollution - Ebtekar, Sayed Sarwar (Journal of Natural Sciences – Kabul University, 2025)
Due to the growing problems of air pollution and the importance of environmental issues, controlling particle release and its conditions is crucial. Electrical and mathematical models of electrostatic precipitators in the physical cleaning of particles are vital in this study and are widely used in industries related to emitted particles, such as cement, dry and wet air cleaning, and metallurgical industries. In this paper, according to the electrical model of electrostatic precipitators, electrostatic power, Coulomb's law, Stokes' law, and Ornstein's law are applied in the method of physical purification of polluted air. Additionally, the removal efficiency of contaminated particles by electrical sedimentation is investigated using motion dynamics. This study also explores the electrical models, particle flow, and electric fields used to create charged particles in the depositor's electrical system.